OVIDIANISM AND THE END OF ELEGY IN MAXIMIANUS 5. - Schmidt, Pedro Baroni (Acta Classica, 2022)
Written around the middle of the sixth century CE, the elegiac collection of Maximianus comprises a set of six poems, all of them versifying about the sufferings and impossibilities of love. One of the fifth poem's most prominent features is the use of Ovidian words, images, and themes, specially those drawn from the Amores. These allusions to the Ovidian corpus perform a function of embedding the poem with layers of metapoetical effects. This article explores the intertextual nuances of Maximianus 5 and how they support the reading of the Greek girl as a scripta puella, as a metaphor for the elegiac genre and its tradition, showing how Maximianus' 'Ovidianism' employs elegiac features in order to lament and to decree the death of elegy itself.